Corporate Tax Disclosure in Indonesia: Trends, Content, and Determinants Based on GRI Standard 207 - Aulia, Sandra (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
This study analyzes the trends, content, and factors influencing corporate tax disclosure in Indonesia based on GRI Standard 207. Data were obtained from sustainability reports of companies listed on the Indonesia Stock Exchange for 2021–2023 and analyzed using content analysis, descriptive methods, and panel data regression. The findings show a significant increase in tax disclosure in line with GRI Standard 207 from 2021 to 2023. The financial and energy sectors had the highest disclosure rates, while the technology and property sectors had lower adoption. The "Approach to Tax" (207-1) element was most frequently disclosed, while technical elements like "Country-by-Country Reporting" (207-4) had lower disclosure. The tax disclosure quality index had an average score of 8.529 out of 18, indicating room for improvement. Company size and leverage were significant determinants of tax disclosure, while profitability and company age were not. The study highlights the need for improved tax disclosure, especially in sectors with low adoption, and offers implications for regulators and companies. Future research should expand the scope and explore additional variables.